Design of An Active Power Ankle-Foot Orthosis with Myoelectric Control for Drop-Foot Rehabilitation - Setiawan, Rudi; Sabar, Sabar; Madi, Madi (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2021)
Drop-foot is an inability to lift the foot when walking due to muscle weakness or paralysis. One of the common rehabilitation aids for stroke sufferers with drop-foot is Ankle Foot Orthosis (AFO). This tool serves as a stabilizer for road pattern balance. However, most of the AFO used is passive, so it doesn't help users run properly. Therefore, an active AFO system has been designed as a rehabilitation aid. This AFO is designed with motor control from myoelectric feedback signal (EMG) and also a semi-dynamic ankle joint so that it is more flexible to help the user when stepping. The AFO movement set of to the foot's position in Dorsi and Plantarflexion conditions based on the EMG parameter received by the control unit. Then, the angle sensor standardizes the user's ankle position so that the foot fits the states that have set. This design uses the fuzzy logic method, which functions to control the rotation of the servo motor. The interface system is for monitoring parameters. In this design, pressure sensors (force), EMG, and angle sensors transmitted wirelessly to a computer are used for data analysis under the needs of real-time statistical data processing.